Abundant intratumoral fibrosis prevents lymphocyte infiltration into peritoneal metastases of colorectal cancer. - En Wang (Public Library of Science (PLoS), 2021)
Background Tumor-infiltrating lymphocytes (TILs) have been reported to reflect the anti-tumor immune status. However, recent investigations have demonstrated that intratumoral fibrosis is important as a factor affecting the infiltration of TILs. This study investigated the organ specificities of TIL infiltration and intratumoral fibrosis in primary colorectal cancer and distant metastases, as well as the relationship between the distribution of TILs and intratumoral fibrosis. Methods Patients who underwent resection of primary tumors or distant metastases for colorectal cancer with distant metastases were enrolled. We evaluated the TIL infiltration by immunohistochemical staining with CD3&CD8 and intratumoral fibrosis by immunohistochemical staining with α-SMA positive cancer-associated fibroblasts and Masson's trichrome staining against collagen fibers. The "ImageJ" was used to evaluate fibrosis, and the density of TILs in the dense and sparse areas of fibrosis was calculated. The Immunoscore (IS) was obtained based on the density of CD3+/CD8+TILs in the tumor center and invasive margin of the primary tumor. Results The degree of CD3+/CD8+TIL infiltration in peritoneal metastases was significantly lower than that in liver and lung metastases. The area ratio of α-SMA positive cancer-associated fibroblasts and collagen fibers in peritoneal metastases was significantly higher than that of liver and lung metastases. Furthermore, the density of TILs in the high-fibrosis area was significantly lower than that in the low-fibrosis area. In the high-IS group of primary tumors, the degree of TIL infiltration in distant metastases was significantly higher than that in the low-IS group. Conclusion The infiltration of T lymphocytes into tumors is prevented in peritoneal metastases of colorectal cancer due to the high intratumoral fibrosis, which may lead to treatment resistance and a poor prognosis.